Una travesía conceptual del Matlatzinco al Valle de Toluca - Albores Zárate, Beatriz (Annals of Anthropology, 2009)
The otomiana jurisdiction of the Posclásico, that was located to the west of the river basin of Mexico, is known academically almost only with the Nahuatl name of Matlatzinco. Its approximate territory began to designate itself, in addition, “Toluca Valley”, at the beginning of the Virreinato in century XVI. Since then, the binomial Matlatzinco/Valle de Toluca has been used indifferently with different geographic and jurisdictional contents. In this work I analyze both names, from an historical perspective of its use, as far as four of its meaning: original, initial, restricted and strict. And I expose the geographic-cultural aspects that they define to that outside the average or lacustrine zone of that otomiana jurisdiction –located in the first sub-river basin of the Lerma river–, to which, in strict sense, it is possible to call “Toluca Valley”.